Deteksi dini skoliosis menggunakan skoliometer pada siswa kelas VI SD di Kecamatan Mapanget Manado - Parera, Amy C.; Sengkey, Lidwina S.; Gessal, Joudy (Universitas Sam Ratulangi, 2016)
Abstract: Most of scoliosis has been diagnosed in 10 to 15 year old children. Untreated scoliosis may become worse and may affect the cardiopulmonary function, limited mobilitiy for people and have a negative impact on posture. Early detection of scoliosis plays an important role in preventing deformity and damages. This study aimed to obtain the number of the sixth grader students who were potentially scoliosis in Mapanget Manado. This was an observational descriptive study. Data were collected by measuring the Angle of Trunk Rotation of 81 students of sixth grade who met the inclusion criteria by using scoliometer. The results showed that there were three students (4%) aged 11 years who were highly potential scoliosis. There were 28 of the 37 female students (76%) categorized as intermediate and highly potential scoliosis groups. All students with highly potential scoliosis were from independent school. Conclusion: The percentage of the sixth grader students in Mapanget Manado who were detected as highly potential scoliosis was 4%.Keywords: early detection, scoliosis, scoliometerAbstrak: Sebagian besar skoliosis terdiagnosis pada anak dengan rentang usia 10 hingga 15 tahun. Skoliosis yang tidak ditangani dapat menjadi lebih buruk, berpengaruh pada fungsi kardiopulmoner, keterbatasan mobilitas bagi penderita dan berdampak buruk pada postur tubuh. Deteksi dini skoliosis berperan penting dalam mencegah kelainan dan kerusakan yang bertambah parah. Penelitian ini bertujuan untuk mengetahui jumlah siswa kelas VI SD yang dideteksi berpotensi skoliosis di Kecamatan Mapanget Manado. Metode: Penelitian ini bersifat observasional deskriptif. Data diperoleh melalui pengukuran langsung Angle of Trunk Rotation pada 81 siswa kelas VI SD yang memenuhi kriteria inklusi dengan menggunakan alat skoliometer. Hasil penelitian mendapatkan tiga siswa (4%) berusia 11 tahun yang berpotensi tinggi skoliosis. Terdapat 28 dari 37 orang (76%) siswa perempuan termasuk dalam golongan intermediate dan potensi tinggi skoliosis Semua siswa berpotensi tinggi skoliosis berasal dari sekolah swasta. Simpulan: Persentase jumlah siswa kelas VI SD di Kecamatan Mapanget yang dideteksi berpotensi tinggi skoliosis sebanyak 4%.Kata kunci: deteksi dini, skoliosis, skoliometer.